Nursing Students’ Learning Support, Outcome, and Satisfaction Towards Online Learning - Rustiana Tasya Ariningpraja; Shila Wisnasari (Journal of Nursing Science Update (JNSU), 2023)
Online learning in nursing education has been carried out for a long time by several educational institutions worldwide. However, online learning in Indonesia has been forced to take place since the Coronavirus Disease 2019 pandemic was announced. This study aims to determine how students perceive learning support and how it relates to learning outcomes and student satisfaction in online learning that has been implemented for the even semester of 2021. This study involved 160 respondents willing to participate in filling out statements related to online learning support, Grade Point Average (GPA), and satisfaction. The data were analyzed using the Pearson test. The results showed a positive correlation between support for nursing student satisfaction during online learning (p<0.05). However, this study's support did not correlate with learning outcomes (p>0.05). Most nursing students perceive instructional, lecturer, peer, and technical support positively. A detailed explanation of why the results of this study are important and discussed in the article. In conclusion, educational institutions must periodically evaluate students' perceptions of learning support, which is not only limited to online learning but also blended learning which is likely to be applied. In addition, satisfaction can also help assess how to provide an overview of students' views as regular customers at nursing education institutions.